PKM Pelatihan Pembuatan Bahan Ajar Dengan Menggunakan Aplikasi Canva Bagi Guru di SD Negeri Pampang - Andi Sadriani; Darman Manda; Ernawati S. K (Universitas Negeri Makassar, 2023)
The utilization of technology in the use of learning media holds great importance in the current era. Learning media can take the form of visual, audio, and audiovisual materials. Engaging learning media can create learning activities that are easy to remember and understand. Canva, a graphic design application, assists users in creating various types of creative materials, both online and offline. Using Canva as a learning medium can facilitate teachers in designing learning materials. Almost all teachers at SD Negeri Pampang are unable to create video-based learning media, resulting in limited delivery of content to students. The purpose of this activity is to provide training to teachers at SD Negeri Pampang in creating learning media using Canva. The training is conducted through several stages, namely socialization, practice, and evaluation. The results of this activity indicate that the training participants experience an increase in knowledge and skills related to the use of learning media with the Canva application.